Rigid Bronchoscopy in Foreign Body Aspiration Diagnosis and Treatment in Children - Aleksandra Pietraś; Marcin Markiewicz; Grażyna Mielnik-Niedzielska (MDPI AG, 2021)
Foreign body aspiration in children is a common condition and can bring about serious undesired results. Fast and accurate diagnosis and foreign body extraction from airways are essential. We performed a retrospective study on rigid bronchoscopy outcomes due to suspected foreign body aspiration. A total of 66 children were admitted to the Chair and Department of Pediatric Otolaryngology, Phoniatrics and Audiology, Medical University of Lublin between 2015 and 2020 and underwent rigid bronchoscopy in general anesthesia due to suspected foreign body aspiration. We analyzed the data, including patients age and sex, reported complaints, and bronchoscopy findings. Analyzed children were aged from 8 months to 17 years old; 74.24% of them were under 3 years old during the procedure, and most of the operated patients were males. In 36.36% cases, no foreign body was identified, and 57.14% foreign bodies were located in right main bronchus. A total of 80.95% of foreign bodies extracted from airways were organic, mostly nuts. Diagnosis and treatment of suspected foreign body aspiration requires consistent cooperation between pediatricians, pulmonologists, anesthesiologists, and otolaryngologists.